PENGEMBANGAN MEDIA AUDIO VISUAL PEMBELAJARAN PENATALAKSANAAN ASUHAN KEBIDANAN PERSALINAN - Islahunnufus, Islahunnufus; Wiryotinoyo, Mujiyono; Rusdi, Muhammad (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2012)
This study aims to produce and develop an audio-visual learning media for helping teachers in Management Midwifery Care Delivery of Kala I, II, III and IV. By adapting Borg and Gall’s model (1983), procedures of development includes (1) analysis of the problem, (2) the collection of data, (3) mendesai products, (4) validation of design, (5) revision of design, (6) test cuba products, (7) revision of products, (8) the trial use, (9) revision of the product, and (10) product period. The results of this study as a whole is a product that is developed on both criteria, the following details (1) media Validator gives a value of 4 which means the product at a good level, (2) Validator of material with a value of 4.5 which means that both products are at good levels based on material elements, (3) The response of students about media fascination that was developed had an average score of 4.14 on testing a small group, is included in both criteria. Response field or group of students scored 4.25 grade categorized as good, (4) The trial results showed that the average pre-test students for field trials in the pre-test class IIA shows the average value of 56.7 and mean average post-test grade 76 at IIC pre-test showed 54.48. post-test showed the value of 64.83 calculated on a simple learning outcomes of students with a 10,5 difference between class IIA to IIC This figure shows that the product can provide the difference in student learning Study abroad and thoroughness. In the normal group based on these data we can conclude that audiovisual media learning midwifery care delivery based on the criteria of both the validity and effectiveness of student response and teacher audio visual media users midwifery management of labor. Kata kunci: Audio Visual Media, Learning Management Midwifery Care Delivery